Implementasi Pendidikan Soft Skills dalam Membentuk Moralitas Siswa Madrasah - Nuryanto Nuryanto; Muhammad Badaruddin (Jurusan PGMI FTIK IAIN Metro Lampung, 2019)
This research focused on how the implementation of softskills education in improving students’ character in MAN 1 East Lampung, including the concept and characterists of softskill education, the implementation of soft skill education in improving students’ character, and the influence of softskill education in improving students’ character in MAN 1 East Lampung. This research used a qualitative approach and the type is fenomenology research. The researcher used observation, interview and documentation method in collecting the data. The data were analyzed by some steps; they were reducing the data, presenting the data and conclusion. Having the research, the researcher found some results, they are : 1) The concept and characteristics of softskill education applied in MAN 1 East Lampung used “holistic-integrative” model. It means, both hard skill and softskill were applied integratively by inserting the Islamic values andit was aplied to all school members. 2) The implementation of softskills eduaction in improving students’ character applied through some ways, they are: a) teaching character integratively, b) Islamic habituation program, c) applying practical approach and demontration method, d) Empowering the colaboration to the students’ parent (family) and society enviroment, e) modeling approach by teacher attitudes, and f) extracuriculers activities related to islamic program. The implementation of soft skill education has a significant influence to the improving students’ character. Some proves can be used as the indicator of its program, they are: a) the students’ spiritual awareness to the God, b) Islamic school culture, c) the awareness of students’ dicipline and resposibility.